2017
DOI: 10.1016/j.apergo.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and physiological human responses to simulated and real environments: A comparison between Photographs, 360° Panoramas, and Virtual Reality

Abstract: Psychological research into human factors frequently uses simulations to study the relationship between human behaviour and the environment. Their validity depends on their similarity with the physical environments. This paper aims to validate three environmental-simulation display formats: photographs, 360° panoramas, and virtual reality. To do this we compared the psychological and physiological responses evoked by simulated environments set-ups to those from a physical environment setup; we also assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(140 citation statements)
references
References 88 publications
8
131
0
1
Order By: Relevance
“…HMD VR displays have been shown as suitable in reproducing several aspects of visual perception (e.g. pleasantness, excitement, or interest) in interior spaces when comparing real and virtual reality environments depicting both daylit (Chamilothori et al 2019b) and artificially lit scenes (Abd-Alhamid et al 2019;Higuera-Trujillo et al 2017). However, due the limited luminance range of the display in current HMD VR displays, some aspects of visual perception, such as glare, cannot be investigated.…”
Section: Virtual Reality As An Experimental Tool For Lighting Studiesmentioning
confidence: 99%
“…HMD VR displays have been shown as suitable in reproducing several aspects of visual perception (e.g. pleasantness, excitement, or interest) in interior spaces when comparing real and virtual reality environments depicting both daylit (Chamilothori et al 2019b) and artificially lit scenes (Abd-Alhamid et al 2019;Higuera-Trujillo et al 2017). However, due the limited luminance range of the display in current HMD VR displays, some aspects of visual perception, such as glare, cannot be investigated.…”
Section: Virtual Reality As An Experimental Tool For Lighting Studiesmentioning
confidence: 99%
“…Although well-established questionnaires in terms of motion sickness are widely used, there is one evident drawback of such methods if compared to physiological evaluations; for instance, lengthy questionnaires are generally administered after a user has performed an experiment, therefore he/she has to shift attention away from the experiment and on the contrary has to focus on body feelings [10]. Physiological indicators are developed based on physiological signals such as heart rate variability, blood pressure, electrogastrography and galvanic skin reaction [5,17]. Dennision et al proposed other indicators that were not much studied in the scope of cybersickness, such as stomach activity, blinking and breathing [10].…”
Section: Quantitative Measurementsmentioning
confidence: 99%
“…Several studies found that exposure to virtual environments in VR may have similar effects comparing to those in real environments. [38][39][40][41] Virtual display of natural environments in various settings (eg, forest, urban green space, streetscapes, biophilic indoor space) had been used to detect the effects on stress reduction, attention restoration, and cognitive function. [41][42][43][44] Eye-tracking, combined with VR, provides a unique opportunity to measure people's visual attention to specific elements in a simulated virtual environment by calculating the amount of time individual focuses on specific objects.…”
Section: Introductionmentioning
confidence: 99%